Mitochondrial Genome Diversity in Collembola: Phylogeny, Dating and Gene Order - Chiara Leo; Antonio Carapelli; Francesco Cicconardi; Francesco Frati; Francesco Nardi (Diversity, 2019)
Collembola (springtails) are an early diverging class of apterygotes, and mark the first substantial radiation of hexapods on land. Despite extensive work, the relationships between major collembolan lineages are still debated and, apart from the Early Devonian fossil Rhyniella praecursor, which demonstrates their antiquity, the time frame of springtail evolution is unknown. In this study, we sequence two new mitochondrial genomes and reanalyze all known Collembola mt-genomes, including selected metagenomic data, to produce an improved phylogenetic hypothesis for the group, develop a tentative time frame for their differentiation, and provide a comprehensive overview of gene order diversity. Our analyses support most taxonomically recognized entities. We find support for an Entomobryomorpha + Symphypleona clade, while the position of Neelipleona could not be assessed with confidence. A Silurian time frame for their basal diversification is recovered, with an indication that divergence times may be fairly old overall. The distribution of mitochondrial gene order indicates the pancrustacean arrangement as plesiomorphic and dominant in the group, with the exception of the family Onychiuridae. We distinguished multiple instances of different arrangements in individual genomes or small clusters. We further discuss the opportunities and drawbacks associated with the inclusion of metagenomic data in a classic study on mitochondrial genome diversity.